2017
DOI: 10.5999/aps.2017.01207
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with a Prolonged Length of Hospital Stay in Patients with Diabetic Foot: A Single-Center Retrospective Study

Abstract: BackgroundWe conducted this study to identify factors that may prolong the length of the hospital stay (LHS) in patients with diabetic foot (DF) in a single-institution setting.MethodsIn this single-center retrospective study, we evaluated a total of 164 patients with DF, and conducted an intergroup comparison of their baseline demographic and clinical characteristics, including sex, age, duration of diabetes, smoking status, body mass index, underlying comorbidities (e.g., hypertension or diabetic nephropathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In addition, once accumulated, uremic toxins lead to phagocytic dysfunction. Therefore, these patients are disposed to developing impaired infection control (Choi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, once accumulated, uremic toxins lead to phagocytic dysfunction. Therefore, these patients are disposed to developing impaired infection control (Choi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…17 The other study about length of hospital stay in diabetic foot found that WBC count, CRP levels, and albumin levels were strongly correlated with long term hospital stay. 18 Furthermore, poor prognosis predictors decremental albumin levels and incremental HbA1c are strongly related with elevated plasma protein glycation that irreversibly impairs the wound healing physiology from cells-to-organs. Also wound healing mechanisms; as migration, proliferation, and transdifferentiation steps are affected due to the toxic effects of impaired blood glucose control.…”
Section: Discussionmentioning
confidence: 99%
“…These are factors that commonly affect the physiological reserve of the patients. Co-morbidities, malnutrition, anemia among others are usually considered to play a role in such patients [ 7 ]. The patients enrolled in the study therefore all had normal serum albumin, adequate hematocrit and normal sugar levels.…”
Section: Introductionmentioning
confidence: 99%